2020
DOI: 10.1021/acs.cgd.0c00044
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective of Gallic Acid on Calcium Oxalate Nucleation

Abstract: The therapeutics for nephrolithiasis have created an awareness of the potential effects of crystal modifiers on the biocrystallization process. The crystallization of calcium oxalate, a primary constituent of kidney stones, is confirmed to be inhibited by natural or synthetic modifiers, but the induction of calcium oxalate dihydrate and trihydrate, which is likewise effective for retardation of stone formation, is rarely focused on. Herein, we performed a systematic investigation of the effect of gallic acid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The oxidation peak of GA was confirmed with the addition of GA in both samples (c = 0.02 mM) where a more pronounced broad shoulder was observed at the same potential (E = 0.34 V) in both samples, which confirms that GA was captured in calcium oxalate clusters. The obtained data agree with the literature, since, in pure hydrate form (run 15), the adsorption of GA did not occur, while in the other two runs (runs 15 and 17), where the presence of GA resulted in a mixture of three hydrate forms, gallic acid was captured in the calcium oxalate clusters [22]. It was also observed that, if the proportion of individual hydrates is less than 10%, GA will not be visible in the cyclic voltammogram (Figure S2).…”
Section: Cyclic Voltammetrysupporting
confidence: 89%
See 2 more Smart Citations
“…The oxidation peak of GA was confirmed with the addition of GA in both samples (c = 0.02 mM) where a more pronounced broad shoulder was observed at the same potential (E = 0.34 V) in both samples, which confirms that GA was captured in calcium oxalate clusters. The obtained data agree with the literature, since, in pure hydrate form (run 15), the adsorption of GA did not occur, while in the other two runs (runs 15 and 17), where the presence of GA resulted in a mixture of three hydrate forms, gallic acid was captured in the calcium oxalate clusters [22]. It was also observed that, if the proportion of individual hydrates is less than 10%, GA will not be visible in the cyclic voltammogram (Figure S2).…”
Section: Cyclic Voltammetrysupporting
confidence: 89%
“…ions possibly interact with C 2 O 4 2− and GA − leading to the formation of calcium oxalate clusters by specific interactions [22]. This could potentially indicate that gallic acid could be an efficient inhibitor or modulator towards obtaining specific hydrate modifications of calcium oxalate.…”
Section: The Influence Of the Process Parameters On The Obtained Calcium Oxalate Hydrate Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of COD may be due to the inhibitor affecting the nucleation and growth process of CaOx and the presence of proteins stabilizes the existence of the COD form. Li et al 43,44 believed that the presence of additives such as citric acid can alter this crystallization pathway by modulating the water activity and the intermolecular interactions.…”
Section: Natural Macromolecular Inhibitors Of Caox Crystallizationmentioning
confidence: 99%
“…Crystal growth modifiers are small amounts of additives that can be used to either promote or inhibit crystallization/transformation processes. Several types of additives, such as amino acids [21][22][23][24][25][26][27][28], proteins [29,30], carboxylic acids [31][32][33] and polymers [34][35][36] have been shown to affect CaOx crystallization. In addition, studies have shown that peptides containing aspartic acidglutamic acid, glutamic acid-glutamic acid, alanine-aspartic acid amino acids have a profound effect on the CaOx crystals and could promote the formation of COD and COT crystals and stabilize these metastable phases over very long periods of time [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%